Providing compassionate care via eHealth - Su, Jing Jing (Nursing ethics, 2024)
BackgroundeHealth was widely used during the COVID-19 pandemic. Much attention was given to the technical aspects of eHealth, such as infrastructure and cost, while the soft skill of compassion remained underexplored. The wide belief in compassionate care is more compatible with in-person interactions but difficult to deliver via e-platforms where personal and environmental clues were lacking urges studying this topic.Purposeto explore the experience of delivering compassionate care via an eHealth platform among healthcare professionals working to contain the COVID-19 pandemic.MethodsA qualitative study design with an interpretative phenomenological analysis approach was used. Twenty healthcare professionals (fifteen nurses and five physicians) who provided care using technology platforms, such as telephone hotlines, mobile apps, and social media, were interviewed individually.Ethical considerationsPermission to conduct the study was obtained from the Institutional Review Board.ResultsParticipants stated that “eHealth enabled compassionate care during the pandemic” by ensuring patient care availability and accessibility. They shared experiences of “communicating compassionate care via eHealth” with suggestions of addressing patients’ needs with empathy, adopting a structured protocol to guide eHealth communication, and using more advanced visual-media methods to promote human-to-human interaction. They recommended “setting realistic mutual expectations” considering the limitations of eHealth in handling complex health situations and staffing shortages. Participants considered “low eHealth literacy hinders compassion.” Additionally, they recommended the need for “institutional/system-level support to foster compassionate care.”ConclusionParticipants recognized the importance of integrating compassion into eHealth services. Promotion of compassionate care requires standardization of eHealth services with institutional and system-level support. This also includes preparing adequate staffing who can communicate compassionate care via eHealth, set realistic expectation, and adjust communication to eHealth literacy level while meeting the needs of their patients.